Novel Pathogenic Variants in PJVK, the Gene Encoding Pejvakin, in Subjects with Autosomal Recessive Non-Syndromic Hearing Impairment and Auditory Neuropathy Spectrum Disorder - Domínguez-Ruiz, María; Rodríguez-Ballesteros, Montserrat; Gandía, Marta; Gómez-Rosas, Elena; Villamar, Manuela; Scimemi, Pietro; Mancini, Patrizia; Rendtorff, Nanna D.; Moreno-Pelayo, Miguel A.; Tranebjaerg, Lisbeth; Medà, Carme; Santarelli, Rosamaria; et al. (Genes, 2022)
Pathogenic variants in the PJVK gene cause the DFNB59 type of autosomal recessive non-syndromic hearing impairment (AR-NSHI). Phenotypes are not homogeneous, as a few subjects show auditory neuropathy spectrum disorder (ANSD), while others show cochlear hearing loss. The numbers of reported cases and pathogenic variants are still small to establish accurate genotype-phenotype correlations. We investigated a cohort of 77 Spanish familial cases of AR-NSHI, in whom DFNB1 had been excluded, and a cohort of 84 simplex cases with isolated ANSD in whom OTOF variants had been excluded. All seven exons and exon-intron boundaries of the PJVK gene were sequenced. We report three novel DFNB59 cases, one from the AR-NSHI cohort and two from the ANSD cohort, with stable, severe to profound NSHI. Two of the subjects received unilateral cochlear implantation, with apparent good outcomes. Our study expands the spectrum of PJVK mutations, as we report four novel pathogenic variants: p.Leu224Arg, p.His294Ilefs*43, p.His294Asp and p.Phe317Serfs*20. We review the reported cases of DFNB59, summarize the clinical features of this rare subtype of AR-NSHI and discuss the involvement of PJVK in ANSD.